(untitled) (Baghdad Science Journal, 2016)
In this paper some chalcones (C1-C8) are prepared based on the reaction of one mole of substituted acetophenone with one mole of substituted benzaldehydes in the presence of (40%) sodium hydroxide as a base. Pyrazolines (P1–P8) are prepared from the reaction of chalcones (C1-C8) with hydrazine hydrate. Isoxazoline (I1-I8) is prepared from the reaction of chalcones (C1-C8) with hydroxyl amine hydrochloride in the presence of (10%) sodium hydroxide as a base. These compounds are characterized by using various physical and spectral methods. The compounds are screened for their in vitro antibacterial activity using gram-positive bacteria and gram-negative bacteria. Several derivatives of pyrazolines and isoxazolines are produced well to moderate activities against number of bacteria.